Entrepreneurial Careers: Determinants, Trajectories, and Outcomes - Adrián Luis Mérida Gutiérrez (Copenhagen Business School (CBS), 2019)
How do the careers of entrepreneurs differ from the rest? Which pathways lead to and result from entrepreneurship? Is entrepreneurial experience valued in the labor market? Despite the increasing attention that the topic of entrepreneurship has captured from scholars across different fields, these and many other questions still remain unsolved. As challenging as it might be, finding answers for such questions is paramount not only to strengthen the current knowledge in the academic literature, but also in light of the increasing interest from policy makers in encouraging entrepreneurial activities. Based on rich observational data from the registers of Denmark and using advanced econometric techniques, this thesis intends to contribute to the extant knowledge on the determinants and outcomes of an entrepreneurial experience by means of three different essays.
hdl:10398/9718
Keywords: 650